If a , b and c are complex numbers such that:
a 2 + b 2 + c 2 = 2 5 a 3 + b 3 + c 3 = 1 0 6 a 4 + b 4 + c 4 = 4 7 7 a + b + c ∈ N
Then we let: x + y + z = a 5 + b 5 + c 5 + 1 7 x y + x z + y z = a 7 + b 7 + c 7 − 4 2 x y z = a 6 + b 6 + c 6 + 5 1
Find ⌊ ∣ ( x − y ) ( y − z ) ( z − x ) ∣ ⌋ .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
A little long? Waiting for a very long recursion reloaded. :D
Could u just explain me the last three steps??
Problem Loading...
Note Loading...
Set Loading...
Let S 1 = a + b + c , S 2 = a b + a c + b c , S 3 = a b c and P n = a n + b n + c n .
By Newton's Sums we know:
P 1 = S 1
P 2 = P 1 S 1 − 2 S 2 = S 1 2 − 2 S 2
P 3 = P 2 S 1 − P 1 S 2 + 3 S 3 = S 1 3 − 3 S 1 S 2 + 3 S 3
P n = P n − 1 S 1 − P n − 2 S 2 + P n − 3 S 3
Hence, P 4 = P 3 S 1 − P 2 S 2 + P 1 S 3 = S 1 4 − 4 S 1 2 S 2 + 4 S 1 S 3 + 2 S 2 2
With the known values the following system is formed:
S 1 2 − 2 S 2 = 2 5
S 1 3 − 3 S 1 S 2 + 3 S 3 = 1 0 6
S 1 4 − 4 S 1 2 S 2 + 4 S 1 S 3 + 2 S 2 2 = 4 7 7
From the first equation, solve for S 2 :
S 2 = 2 S 1 2 − 2 5
Substitute in the second equation, simplify and solve for S 3 :
S 1 3 − 3 S 1 ( 2 S 1 2 − 2 5 ) + 3 S 3 = 1 0 6 ⟹ S 3 = 6 S 1 3 − 7 5 S 1 + 2 1 2
Substitute S 2 and S 3 in the third equation:
S 1 4 − 4 S 1 2 ( 2 S 1 2 − 2 5 ) + 4 S 1 ( 6 S 1 3 − 7 5 S 1 + 2 1 2 ) + 2 ( 2 S 1 2 − 2 5 ) 2 = 4 7 7
Expand and simplify:
S 1 4 − 1 5 0 S 1 2 + 8 4 8 S 1 − 9 8 7 = 0
Using the rational root test it factors as:
( S 1 − 7 ) ( S 1 3 + 7 S 1 2 − 1 0 1 S 1 + 1 4 1 ) = 0
The second factor doesn't have natural solutions, hence S 1 = 7 .
Obtain S 2 and S 3 :
S 2 = 2 S 1 2 − 2 5 = 2 7 2 − 2 5 = 1 2
S 3 = 6 S 1 3 − 7 5 S 1 + 2 1 2 = 6 7 3 − 7 5 ( 7 ) + 2 1 2 = 5
Now, obtain P 5 , P 6 and P 7 :
P n = 7 P n − 1 − 1 2 P n − 2 + 5 P n − 3
P 5 = 7 P 4 − 1 2 P 3 + 5 P 2 = 7 ( 4 7 7 ) − 1 2 ( 1 0 6 ) + 5 ( 2 5 ) = 2 1 9 2
P 6 = 7 P 5 − 1 2 P 4 + 5 P 3 = 7 ( 2 1 9 2 ) − 1 2 ( 4 7 7 ) + 5 ( 1 0 6 ) = 1 0 1 5 0
P 7 = 7 P 6 − 1 2 P 5 + 5 P 4 = 7 ( 1 0 1 5 0 ) − 1 2 ( 2 1 9 2 ) + 5 ( 4 7 7 ) = 4 7 1 3 1
Hence:
x + y + z = 2 1 9 2 + 1 7 = 4 7
x y + x z + y z = 4 7 1 3 1 − 4 2 = 2 1 7
x y z = 1 0 1 5 0 + 5 1 = 1 0 1
Finally, let P ( m ) have roots x , y and z :
P ( m ) = ( m − x ) ( m − y ) ( m − z ) = m 3 − ( x + y + z ) m 2 + ( x y + x z + y z ) m − x y z
P ( m ) = m 3 − 4 7 m 2 + 2 1 7 m − 1 0 1
By definition, the discriminant of P ( m ) = m 3 + b m 2 + c m + d is:
Δ = b 2 c 2 − 4 c 3 − 4 b 3 d + 1 8 b c d − 2 7 d 2 = ( x − y ) 2 ( y − z ) 2 ( z − x ) 2
So, ( x − y ) 2 ( y − z ) 2 ( z − x ) 2 = ( − 4 7 ) 2 ( 2 1 7 ) 2 − 4 ( 2 1 7 ) 3 − 4 ( − 4 7 ) 3 ( − 1 0 1 ) + 1 8 ( − 4 7 ) ( 2 1 7 ) ( − 1 0 1 ) − 2 7 ( − 1 0 1 ) 2 = 3 9 4 6 8 2 1 2
And finally:
⌊ ∣ ( x − y ) ( y − z ) ( z − x ) ∣ ⌋ = ⌊ 4 3 9 4 6 8 2 1 2 ⌋ = 7 9